Pathological tau interactors and their role in propagation and neurodegeneration. (20th December 2022) - Martínez, Pablo; Patel, Henika; You, Yanwen; Garfe, Nur Jury; Perkins, Abigail; You, Yingjian; Huang, Xiaoqing; Dutta, Sayan; Wijeratne, Aruna; Redding, Javier; Mosley, Amber L.; Rochet, Chris; et al.
Abstract: Background: Tau aggregates are critical pathological features of Alzheimer's disease (AD) and other tauopathies. An important focus of research has been to understand the pathological tau propagation in AD patient brains that follow neuronal networks. Despite the knowledge acquired, the cellular mechanism involved in tau propagation and seeding are still unclear. Unfortunately, the nature of the tau species involved in the spreading and the precise seeding/template remains unknown. Despite this uncertainty, some studies suggest that a high molecular weight tau (HMW‐tau) is the form of tau involved in trans‐synaptic propagation. It remains unresolved whether these HMW‐tau particles are made exclusively of tau or contain other constituents such as proteins necessary for propagation. Method: 3‐months‐old PS19 mice (n=3). TBS‐soluble PS19 brain extracts were passed through a Size Exclusion Chromatography (SEC) column. We then measured the tau seeding activity of each SEC‐fraction using a well‐described bio sensor cell line that relies on flow cytometry detection of FRET signal. To identify other constituents or interactors of this tau‐ seed, we IP human tau using the HT7 antibody from the fraction with highest tau seeding activity and subjected it to TMT‐tag quantitative Mass Spectrometry. Through quantitative Mass Spectrometry, we were able to identify the protein‐interactome of the tau‐ seed and the interactome of monomeric tau isolated from the same brains. Result: We determined that tau from fraction‐9 (F9) forms an HMW‐tau complex in vivo (>2, 000KDa) with the strongest seeding activity. Interestingly, the tau present in F9 is less than 4.4% of the total tau in the brain of PS19 mice and adopt a protofibrillar morphology. Bioinformatics from both interactomes revealed an enrichment of a specific set of proteins in the tau‐seed in comparison with monomeric tau. Conclusion: HMW‐Tau, which represent the 4% of total tau in PS19 brains, has the highest seeding activity. The protein interactome of this HMW‐tau also differs from the monomeric tau interactome.